Differential Effects of Aripiprazole and Amisulpride on Negative and Cognitive Symptoms in Patients With First-Episode Psychoses - Nielsen, Mette Ødegaard; Kristensen, Tina Dam; Borup Bojesen, Kirsten; Glenthøj, Birte Y.; Lemvigh, Cecilie K.; Ebdrup, Bjørn H. (Frontiers in Psychiatry, 2022)
Introduction: Aripiprazole is hypothesized to have an effect on negative and cognitive symptoms in schizophrenia. Likewise, amisulpride is one of the only second-generation antipsychotics where an effect on negative symptoms has been reported. In the present study, we compare the effect of aripiprazole and amisulpride in initially antipsychotic-naïve patients with first episode psychoses. Methods: Psychopathology and cognitive measures from two consecutive cohorts of antipsychotic-naïve first episode psychotic patients were obtained before and after six weeks of antipsychotic monotherapy with either aripiprazole or amisulpride. Matched healthy controls were included to account for retest effects on the cognitive measures. Analyses of variance (Repeated measures ANOVA) were performed to detect effect of time and possible cohort*time interactions. Results: Longitudinal data was obtained from 47 and 48 patients treated for six weeks with amisulpride or aripiprazole, respectively. For the Wallwork negative symptom dimension, there was a cohort*time interaction (F1,93=4.29, p=0.041) and a significant effect of time (F1,93=6.033, p=.016) which was driven by an improvement in patients treated with aripiprazole (t47=4.1, p<.001), and not observed in patients treated with amisulpride (p>0.5). For the eight cognitive measures, no cohort*time interaction was found, neither was cognitive improvement in any of the cohorts when accounting for retest effect. Conclusion: Patients treated with aripiprazole improved on negative symptoms, which was not the case for patients treated with amisulpride. This may point to a general effect of partial D2 receptor agonist on negative symptoms, in patients with first episode psychoses. There was however no improvement in cognitive functions.